Social Deixis in The Chronicles of Narnia: Prince Caspian Movie Script - Pawanna, Stevani; Abeng, Andi Tenri; Maca, Sudirman (Fakultas Sastra, Universitas Bosowa, 2024)
This research aims to analyze the types of social deixis used in The Chronicles of Narnia: Prince Caspian movie script, and to describe the referential meaning of each type of social deixis used in The Chronicles of Narnia: Prince Caspian movie script using descriptive analysis method. The result shows that there are 6 types of social deixis used in The Chronicles of Narnia: Prince Caspian movie script, they are person marking, speech levels, formal distinctions, different in names, titles, and kinship designation, linguistic performance that is count as social act and linguistic performance that can accompany the social act. The writer found 982 expressions of social deixis where the most frequently used category is the person marking. Other types that are also found The Chronicles of Narnia: Prince Caspian movie script are speech level formal distinction of utterance different ways which names, titles and kinship relationships designated, social acts and expressions that complete social acts. The referential meaning in this research, were took one examples of each type data of social deixis that has been found in the movie script